2015
DOI: 10.1007/s10508-014-0457-1
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparative Analysis of a Community and General Sample of Lesbian, Gay, and Bisexual Individuals

Abstract: Samples recruited at lesbian, gay, and bisexual (LGB) venues have certain benefits, but a major drawback is that these samples are prone to bias as they only contain LGB participants who visit such venues. Empirical data with regard to the potential differences between LGB community samples and LGB general samples may shed some light on the generalizability of research findings from convenience samples recruited through LGB venues. The current study attempted to contribute to existing knowledge by examining di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 16 publications
5
50
0
Order By: Relevance
“…Lesotho participants in the earlier waves were also more likely to have disclosed their sexual practices to family members. These findings are similar to the results from a previous study conducted in the Netherlands, which found that participants recruited from lesbian, gay and bisexual venues were more likely to be open about their sexual orientation and to encounter more social stigma related to their sexual orientation, as compared with lesbian, gay and bisexual individuals recruited from a general research panel 28. In particular, stigma may be greater for MSM who are open about their sexual orientation because they may display mannerisms less aligned with traditional male gender roles 29 30.…”
Section: Discussionsupporting
confidence: 89%
“…Lesotho participants in the earlier waves were also more likely to have disclosed their sexual practices to family members. These findings are similar to the results from a previous study conducted in the Netherlands, which found that participants recruited from lesbian, gay and bisexual venues were more likely to be open about their sexual orientation and to encounter more social stigma related to their sexual orientation, as compared with lesbian, gay and bisexual individuals recruited from a general research panel 28. In particular, stigma may be greater for MSM who are open about their sexual orientation because they may display mannerisms less aligned with traditional male gender roles 29 30.…”
Section: Discussionsupporting
confidence: 89%
“…LGBT nonprobability community participants were younger, had more often an exclusive same-sex orientation, and were more open about their sexual orientation (Kuyper, Fernee, & Keuzenkamp, 2016). They also reported more high-risk sexual behavior (Dodds, Mercer, Mercey, Copas, & Johnson, 2006;Evans, Wiggins, Mercer, Bolding, & Elford, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies oversampled from university or urban community sources (e.g., while others relied on online survey participants (e.g., Peters et al, 2007). This may have produced some sampling biases, common in research with difficult-to-reach or minority populations (Kuyper et al, 2016).…”
Section: Discussionmentioning
confidence: 99%